A review of interventions to reduce pain in chronic wounds. (1st December 2019) - Snelgrove, Helen; Baileff, Anne
Abstract : Reduction of chronic wound pain has the potential to improve patients' quality of life, expedite the healing process and, ultimately, relieve pressure on community services. Despite this, education on pain assessment in the management of chronic wounds is lacking. This literature review seeks to provide evidence-based recommendations to reduce chronic wound pain and inform the practice of community nurses. The results of a thematic analysis indicate that a honey dressing or native collagen matrix dressing and conditioning exercises for the lower leg can reduce pain, and nitroglycerin ointment is especially effective. The review also highlights the need for an individualised approach to the assessment and treatment of pain in patients with chronic wounds.